(untitled) (AmS-Varia, 2020)
This article discusses the meaning of stones and the practice of gathering stones, in graves, clearance cairns and stone-covered hillocks. The emphases are on stone-covered hillocks and their long-term usage (up to 1500 years), analyzed using the concept of longue durée. In this paper I propose that the stones in themselves have a cultic meaning as well as the actions, i.e. the remodeling of hillocks and the placing of clearance cairns among graves. In this, I see a connection between stone-covered hillocks, graves and clearance cairns. The underlying concept is a stable, but slowly changing, prehistoric religious tradition that lasted from the Bronze Age to the Migration Period and possibly also through the Late Iron Age. A basic change in this does not take place until the coming of Christianity in the Medieval Period. The reason that Medieval and later clearance cairns were placed together with graves is probably due to their similar appearance.